Sub-inhibitory cefsulodin sensitization of E. coli to β-lactams is mediated by PBP1b inhibition. - Sujoy K Sarkar (Public Library of Science (PLoS), 2012)
The combination of antibiotics is one of the strategies to combat drug-resistant bacteria, though only a handful of such combinations are in use, such as the β-lactam combinations. In the present study, the efficacy of a specific sub-inhibitory concentration of cefsulodin with other β-lactams was evaluated against a range of Gram-negative clinical isolates. This approach increased the sensitivity of the isolates, regardless of the β-lactamase production. The preferred target and mechanism of action of cefsulodin were identified in laboratory strains of Escherichia coli, by examining the effects of deleting the penicillin-binding protein (PBP) 1a and 1b encoding genes individually. Deletion of PBP1b was involved in sensitizing the bacteria to β-lactam agents, irrespective of its O-antigen status. Moreover, the use of a sub-inhibitory concentration of cefsulodin in combination with a β-lactam exerted an effect similar to that one obtained for PBP1b gene deletion. We conclude that the identified β-lactam/cefsulodin combination works by inhibiting PBP1b (at least partially) despite the involvement of β-lactamases, and therefore could be extended to a broad range of Gram-negative pathogens.